How do you solve 2x - \frac { 1} { 2} ( 6+ 2x ) = 7?

2 Answers
May 29, 2017

2x-x=7+3. Therefore x=10

Explanation:

Arrange your equation:

2x - (6/2) - (2x)/2 = 7

2x - x = 7+3

x=10

Thisis your answer x=10

May 29, 2017

x = 10

Explanation:

2x - 1/2 xx (6 + 2x) = 7

We can use some simple algebra to find this.

2x - 1/2 (6 + 2x) = 7

2x - 3 - 1x = 7

2x - x - 3 = 7

x - 3 = 7

x = 7 + 3

color(blue)(x = 10

We can prove this by substituting x for 10 in the equation.

2 xx 10 - 1/2 xx (6 + 2 xx 10) = 7

20 - 1/2 xx (6 + 20) = 7

20 - 1/2 xx 26 = 7

20 - 13= 7